Improvement of radiocephalic fistula maturation: rationale and design of the Liposomal Prednisolone to Improve Hemodialysis Fistula Maturation (LIPMAT) study – a randomized controlled trial. Issue 1 (March 2017) - Voorzaat, Bram M.; van Schaik, Jan; van der Bogt, Koen E.A.; Vogt, Liffert; Huisman, Laurens; Gabreëls, Bas A. Th. F.; van der Meer, Irene M.; van Eps, Randolph G.S.; Eefting, Daniël; Weijmer, Marcel C.; Groeneveld, Han O.; van Nieuwenhuizen, Roos C.; et al.
Background: Non-maturation is a frequent complication of radiocephalic arteriovenous fistulas (RCAVF). In an animal model, liposomal prednisolone improved maturation of experimental fistulas. The Liposomal Prednisolone to Improve Hemodialysis Fistula Maturation (LIPMAT) study investigates if liposomal prednisolone improves RCAVF maturation. Methods and results: The LIPMAT study is an investigator-initiated, multicenter, double-blinded, placebo-controlled randomized controlled trial with 1:1 randomization to liposomal prednisolone or placebo. Eighty patients receiving an RCAVF will be included. The primary outcome is the cephalic vein diameter six weeks after surgery, measured by ultrasound. The LIPMAT study started in May 2016. Enrollment is expected to be completed by the end of 2017. Conclusions: The LIPMAT study is the first to evaluate the efficacy of liposomal prednisolone to enhance RCAVF maturation.